2018
DOI: 10.1080/17482631.2018.1505397
|View full text |Cite
|
Sign up to set email alerts
|

Ways of coping with excessive academic stress among Korean adolescents during leisure time

Abstract: Purpose: Korean adolescents are under excessive academic pressure because of the competitive college entrance examination. This study examined the characteristics of coping strategies on the academic stress experienced by senior high school students in Korea. Methods: A total of 11 adolescents who were preparing for the college entrance examination participated in this study. This study employed semi-structured in-depth interviews. A constructive grounded theory was employed to capture the characteristics of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 48 publications
2
24
0
5
Order By: Relevance
“…Brick, Seely e Palermo (2010) sugerem que essa população está particularmente em risco com perda e má qualidade do sono. Além disso, a crença de que eles podem compensar a privação de sono dormindo longas horas no fim de semana podem perpetuar em dificuldades crônicas do sono (Brown, Buboltz, & Soper, 2002;Park & Kim, 2018). Essas dificuldades podem contribuir para o desgaste físico, emocional, social e acadêmico (Armstrong, Dearden, Kobayashic, & Nagase, 2018;Kent, Uchino, Cribbet, Bowen, & Timothy, 2015).…”
unclassified
“…Brick, Seely e Palermo (2010) sugerem que essa população está particularmente em risco com perda e má qualidade do sono. Além disso, a crença de que eles podem compensar a privação de sono dormindo longas horas no fim de semana podem perpetuar em dificuldades crônicas do sono (Brown, Buboltz, & Soper, 2002;Park & Kim, 2018). Essas dificuldades podem contribuir para o desgaste físico, emocional, social e acadêmico (Armstrong, Dearden, Kobayashic, & Nagase, 2018;Kent, Uchino, Cribbet, Bowen, & Timothy, 2015).…”
unclassified
“…As for conlusion, this research clarified that exam-related stress was prevalent and relevant among students, the need toward future research regarding ways of coping during examination week and analysis about it is extremely recommended as knowledge about effective coping strategies during examination will help them release tense and stress, feel relaxed and positive when they sit for exam (Aldwin et al, 1996;Austin et al, 2010;Berry & Kingswell, 2012;Krohne, 2002;Lazarus & DeLongis, 1983;Martyn-Nemeth, Penckofer, Gulanick, Velsor-Friedrich, & Bryant, 2009;Park & Kim, 2018). As consequences, not only do the students have great opportunity to academically excel, they grow to be mentally health persons.…”
Section: Resultsmentioning
confidence: 91%
“…Kahn & Meyer, 2006;Krohne, 2002). Relating to that, a vast amount of literature and studies linked to stress among students have been well documented and have cited that school as major contributor to the development of students' stress (Barker et al, 2016;Park & Kim, 2018). Scientific studies revealed that majority of students in all parts of the world including Indonesia are mainly dealing with academic issues, and the imprudent academic pressure to perform better specifically during examination are quite high in this country (Taufik, Ifdil, & Ardi, 2013;Wardana & Dinata, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recreational activities play multiple roles in the lives of individuals including reducing stress, promoting relaxation, social support and wellbeing (Kerr et al, 2012;Roberts, 2014;Park & Kim, 2018;Kusi et al, 2018;Coleman & Iso-Ahola, 1993;Addison & Yankyera, 2015). According to Maddi and Khoshaba (2005); Lemay, Hoolahan, & Buchanan (2018) and Riley & Park (2015) physical activities and meditation are effective resources for managing work-related stresses which can lead to effective work climate.…”
Section: Recreationmentioning
confidence: 99%